Peranan Bidang Studi Aqidah Akhlaq dalam Membentuk Kepribadian Anak Didik di MTs. Al-Muhsinin Selak Ampan Pijot - Mustakim, Mustakim (MASALIQ, 2021)
The purpose of this study was to determine the role of the field of study of moral aqidah in shaping the personality of students. This type of research is qualitative, while the research approach used is ethno-methodology. The results of the study indicate that there are several forms of problems faced in shaping the personality of students through moral aqidah lessons at Madrasah Tsanawiyah Al-Muhsinin Selak Ampan Pijot Tengah including: (a). Lack of parental supervision, parents are very decisive because religious education is different from other lessons, where religious education is not only memorized but needs to be lived and practiced. Therefore, parents must supervise their children at home so that what they aspire to it can be achieved. (b). Environmental problems, their parents are farmers and some are traders so that at certain times children are involved in working to help their parents, this also prevents children from studying or attending school. In this case, it is suggested as a parent not to involve their children to work during school hours, but to be given the opportunity to do work after school or during holidays. The efforts made in moral development in MTs. Al-Muhsinin Selak Ampan Pijot of which are as follows: (1). curricular activities and (2). Non-curricular activities.